Effect of pods' position on the protein content in soybean grains at low latitude - Paulo Victor Gomes Sales (Journal of Bioenergy and Food Science, 2016)
Soybean grains have a high protein content, which can vary depending on various factors, as the pods' position throughout the plant. In this sense, aiming to study the effect of pods' position on the main stem of the plant for grades of soybean proteins, It has been accomplished in the years 2010 and 2011, a trial with ten soybean cultivars in the experimental area of the Federal University of Tocantins in Palmas. The experimental area was randomized blocks with 30 treatments and three replications. Treatments were arranged in one a split plot, being allocated in Ten cultivars plots (BRS Valuable, P98Y51, P98Y70, P99R03, M8527RR, M8925RR, M9144RR, M8867RR, and TMG103RR), and the sub plots In the pods' position on the plant (upper third, intermediate, and basal third). According to the results, we can conclude that there is variability among the pods' position. The grains located in the median and apical plant showed a trend of higher protein content. Cultivar P98Y70 showed the highest protein value. In the sampling grain for protein quantitation, it is recommended to use grains of pods located at the same position of the plant.